Effect of intragastric pH on mucosal protective action of sucralfate. Issue 10 (October 1988) - Danesh, J Z; Duncan, A; Russell, R I; Mitchell, G
Abstract : Acid intragastric pH is believed to be mandatory for mucosal protective action of sucralfate, but evidence for its efficacy at neutral pH is lacking. The effect of sucralfate on gastric mucosal erosions induced by oral administration of aspirin and bile acids at acidic pH of 1.5 and 3.9, and near neutral pH of 6.5 was investigated in 320 rats. The effect of sucralfate on the intragastric pH four hours after the ingestion of test solutions was also examined. The incidence and severity of mucosal erosions induced by aspirin and bile acids were lower in animals treated with sucralfate at acidic (p less than 0.001) and near neutral (p less than 0.01) intragastric pH. Mucosal protection was greater with ingestion of sucralfate 300 mg/kg and 200 mg/kg, than with 100 mg/kg. The intragastric pH was higher (p less than 0.001) in sucralfate treated groups at pH 3.9 and 6.5. This study provides evidence that sucralfate protects against mucosal injury at near neutral, as well as at acidic pH.